2020
DOI: 10.1080/13696998.2020.1830782
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in Spain: analysis of patient characteristics, incidence and direct medical costs (2011–2017)

Abstract: Objectives: To review the characteristics of patients with chronic kidney disease (CKD) who attended primary and specialized care centers in Spain, and to analyze patients' use of medical resources and direct medical costs of specialized care. Methods: Records of patients with CKD admitted to primary and specialized healthcare centers in Spain between 2011 and 2017 from two national discharge databases were analyzed in a retrospective multicenter observational study. Records were classified into one-to-five CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Unitary resource costs were obtained from local databases with cost information. 26,27 Disease management cost were identified in scientific literature [27][28][29][30] (Table 4). All costs are expressed in euros (€), A structured questionnaire that included the values identified in the scientific published literature was designed and individually filled by each of the experts.…”
Section: Analytical Procedures Of Results and Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unitary resource costs were obtained from local databases with cost information. 26,27 Disease management cost were identified in scientific literature [27][28][29][30] (Table 4). All costs are expressed in euros (€), A structured questionnaire that included the values identified in the scientific published literature was designed and individually filled by each of the experts.…”
Section: Analytical Procedures Of Results and Costsmentioning
confidence: 99%
“…T A B L E 3 Markov model transition probabilities per 3-month model cycle. €549.13 28,30 MI follow-up in patients with CKD stage 3b-4 with AKI € 2,881.16 29,30 Abbreviations: AKI, acute kidney injury; CKD, chronic kidney disease; MI, myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other contributors to total CKD cost included primary care visits, specialized visits, and diagnostic tests. It has been reported that not only the costs of specialized care decrease with the length of hospital stay reduction [ 19 ], but also a nephrologist/nurse-based multifaceted intervention for stage 3 to 4 CKD patients may be a cost effective approach [ 49 ], suggesting that an integrated management of CKD patients in both specialist and primary care settings is warranted to reduce CKD burden.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the knowledge about CKD-related costs is mandatory to ascertain how CKD management can be improved, leading to a significant decrease in CKD burden [ 5 , 11 18 ]. Unfortunately, data about the impact of CKD on health care costs in Spain are scarce, and most importantly, not focused on a comprehensive approach [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%